Beyond Real and Fake: A Hybrid Visual Authenticity Framework for Generative AI in Creative and Media Ecosystems - Moh. Ali Wisudawan Prakarsa; Aliyah Aliyah; Heri Wijayanto; Zulfah Hasanah; Widya Octary Setiawardhani (Inspire Global Insight Journal, 2026)
The emergence of generative artificial intelligence has radically transformed the production, dissemination, and interpretation of visual media, precipitating a crisis of confidence regarding visual authenticity—a concept historically predicated upon the indexical nature of photography. This research investigates the reconfiguration of visual authenticity within photography, illustration, and packaging design in the age of generative AI, identifying cross-domain thematic regularities to develop a conceptual model of "hybrid visual authenticity." Utilizing an interpretive qualitative methodology and a multiple case study design, this study conducted visual-semiotic analyses of 40 cases and in-depth interviews with 16 practitioners across the fields of photography, illustration, packaging design, and media studies. Analytical procedures incorporated Barthesian semiotic inquiry and Braun and Clarke’s six-stage thematic analysis, employing triangulation of data sources and methodological approaches to ensure rigor. Findings suggest that visual authenticity in the generative AI context transcends the traditional binary of "genuine" versus "fake," manifesting instead as a multifaceted construct shaped by the interplay of creator intent, process transparency, and underlying socio-cultural and regulatory frameworks. Notably, photography and media studies exhibit the strongest emphasis on transparency, whereas illustration and packaging design display greater openness toward human-AI hybrid practices. Accordingly, this study proposes a Hybrid Visual Authenticity Model, synthesizing frameworks of indexicality, aura, and simulacra into a unified analytical lens for diverse creative domains. This research makes both theoretical and practical contributions: it rearticulates classical concepts of visual authenticity for the generative AI paradigm and offers actionable recommendations for design education, professional associations, the packaging sector, and media policymakers.